Empowerment of Village Equipment Through Village Information System Training in Segorotambak Village, Sedati District, Sidoarjo Regency (Future Science, 2021)
The Village Information System (SID) is a web-based application that can facilitate the management of village government information programs and can improve village government administration. Village apparatus as the main potential in providing changes to village development must have adequate capacity in carrying out public services. The main problem with village officials in Segorotambak, Sedati District, Sidoarjo, is that their understanding and skills regarding the management and utilization of village information systems are still not optimal. The purpose of this Community Service is to increase the capacity of village officials in managing the village. Information systems and encourage village government administration. The empowerment method used to help solve this problem is training in the management and utilization of village information systems. The results of this community service show that the training went well and with high enthusiasm, there was an increase in the understanding and skills of village officials in managing and utilizing village information systems based on the SID 3.0 application.